Milly, Molly and Pennyroyal - Pittar, Gill; Morrell, Cris (MM House Pub. Gisborne, N.Z., 2003)
Pennyroyal the cow has a problem with anger, until one day Farmer Hegarty finds a way to help her. Includes teaching guide. Suggested level: junior